ملامح نمو الأنا الشعرية لدى ياسين البكالي في ضوء نظرية ليفينجر (دراسة نفسية نقدية): Developmental Features of Yasin El Bakali's Poetic Ego in Light of Loevinger's Theory (Psycho-critical Study) - براء خالد هلال, (Al Manhal Research Journal, 2023)
Yasin Al-Bakali is a young Yemeni poet possesses an introspective nature, a self-detached disposition, and fervent emotions. He achieves a psychological equilibrium in his poetry, presenting a balanced philosophy. His poetic persona is stable, highlighting Ego prominently, delineating the contours of his emotions, personality traits, and transformations. Importantly, he engages with philosophy both as a life approach and an academic study. This research will delve into the facets of the poetic Ego’s growth according to the theory of self-development, a concept developed by the philosopher Jean Lévinger, originating from the theories of Erik Erikson, and incorporating the ideas of Harry Stack Sullivan, which posit that "The self undergoes a growth process composed of several stages throughout a person's life as a result of dynamic interactions between the internal self and the external environment." In this research, I will observe the growth of this poetic Ego according to the stages proposed by Lévinger, focusing on two collections by Al-Bakali." This study will proceed within the framework of the psychological methodology.